The role of talent management in achieving strategic position: A field study of the opinions of a sample of academic leaders in a number of private universities in the Kurdistan Region of Iraq - Rashavai, Parwar; Gulli, Mehvan (Humanities Journal of University of Zakho, 2022)
The present research aims to determine the role of talent management in achieving a strategic position. The research problem is the extent to which private universities in the Kurdistan Region can achieve a strategic position depending on the dimensions they possess of talent management. The research was based on a set of main and secondary hypotheses that were field-tested in universities. The respondents were (19) universities, and (9) of these universities agreed to distribute the questionnaire to their leaders, and the research included (103) of the academic leaders in the universities surveyed, and the data was collected based on the questionnaire prepared for this purpose, and the data were analyzed using a set of methods Statistics in the program (SPSS V.22). The outcome of the research was to reach several conclusions, the most important of which is the existence of a significant correlation between the dimensions of talent management and the strategic position, and the presence of a significant effect of the dimensions of talent management in achieving the strategic position in the universities surveyed, and in light of the conclusions, several proposals were formulated, the most important of which is that the surveyed universities should pay attention and care More on achieving interaction and communication with other universities to increase the culture and learning processes, which will have positive repercussions on their success. Keywords: talents, talent management, strategic position, private universities in the region.